Innovation Of Assessment Techniques On Maharah Qiraah In Arabic Textbooks Based On Higher Oreder Thingking Skills (HOTS) - Munawarah, Khozinah; Baroroh, R. Umi (Universitas Pahlawan Tuanku Tambusai, 2023)
The reason for this research was conducted in order to analyze and answer the problems in the assessment of class X Arabic books published by the ministry of religion in 2020, especially on qira'ah skills. This research was studied using qualitative methods with library research techniques in collecting data. Primary data comes from Arabic books published by the ministry of religion in 2020, while secondary data comes from documents, both books and related journals. This study aims to describe: (1) techniques for assessing knowledge aspects in Arabic textbooks for class X published by the Ministry of Religion in 2020 (2) techniques for assessing aspects of skills in maharah qira'ah in Arabic textbooks for class X published by the Ministry of Â Religion in 2020 ( 3) innovation analysis Higher Order Thingking Skills (HOTS) assessment of qiro'ah material in Arabic textbooks for class X published by the Ministry of Religion in 2020. The results showed that the assessment that was innovated on the HOTS indicators in the Arabic language book Madrasah Aliyah class X, Ministry of Religion in 2020 indicated that it had fulfilled all content indicators HOTS is at the level of analyzing, evaluating, and creating.